DEVELOPMENT OF BUSINESS ACTIVITY THROUGH TAX BENEFITS IN THE FIELD OF TOURISM (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In this article, information was given about the tax benefits for entrepreneurs currently working in the field of tourism and citizens who want to enter this field. Also, at the same time, problems arising in the field of entrepreneurship due to taxes were studied and suggestions and recommendations were given.